Current aspects of the correlation and improvement of the concepts of crime, criminal misconduct and administrative offense in the legislation of the Republic of Kazakhstan - Amanzholova, Б.А.; Oleinik, В.И. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The problem of studying criminal and administrative responsibility, distinguishing a crime from a criminal offense and an administrative offense is one of the most difficult not only for Kazakhstan, but for the vast majority of post-Soviet states. In this article, the authors analyze the norms of the current criminal legislation of the Republic of Kazakhstan, they studied the practical and theoretical problems of distinguishing the concepts of crime, criminal misconduct and administrative offense, indicate the reasons for their separation, and provide foreign experience in improving these concepts. The authors of this work, taking into account the scientific research of this topical issue by domestic and foreign scientists and practitioners, come to the conclusion that it is necessary to improve and develop a new concept of criminal offense, taking into account modern requirements in society. In addition, the authors make a forecast about possible risks, substantiate the conclusion about the need for a consistent and comprehensive study of the introduced novelties in national legislation. In particular, attention is drawn to the costs of legislative technique, when such important components as doctrinal developments, theoretical validity and criminological forecasting of the introduction of novelties into national legislation are ignored during the development of draft laws.